Psychological Distress Among Occupational Health Professionals During Coronavirus Disease 2019 Pandemic in Spain: Description and Effect of Work Engagement and Work Environment - Ruiz-Frutos, Carlos; Ortega-Moreno, Mónica; Soriano-Tarín, Guillermo; Romero-Martín, Macarena; Allande-Cussó, Regina; Cabanillas-Moruno, Juan Luis; Gómez-Salgado, Juan (Frontiers in Psychology, 2021)
The impact of the COVID-19 pandemic on the mental health of hospital health professionals has been widely described, but few studies have focused on the occupational health professionals. Therefore, the objective of this study is to assess occupational health workers’ psychological distress and its relationship with their work engagement and work environment characteristics. A cross-sectional survey was conducted. A sample of 499 nurses and physicians participated in the study. Variables included demographic data, work environment characteristics, work engagement Utrecht’s Work Engagement Scale (UWES-9) and psychological distress General Health Questionnaire (GHQ-12). Chi-square Automatic Interaction Detection method were performed for data analysis. Data collection took place via internet between April 23 and June 24 2020. 65.53% of the participants had psychological distress and the UWES-9 scale mean score total was 34.80 (SD = 10.69). Workload, conflicts, stressing situations and less job satisfaction were significantly related to a higher percentage of psychological distress (p<0.05). Participants with low engagement showed higher levels of psychological distress (76.7%; p <0.001). Dedication was revealed as the most significant dimension. Interventions aimed at promoting resilience and coping strategies are suggested. Work engagement should be fostered as a preventive measure against psychological distress among occupational health workers. By protecting workers, occupational health departments have a shared responsibility with public health in containing the pandemic. Therefore, it is essential to prevent the psychological impact that this responsibility may have on occupational health workers by implementing prevention measures.